2021
DOI: 10.1038/s41467-021-26844-1
|View full text |Cite
|
Sign up to set email alerts
|

Transient mTOR inhibition rescues 4-1BB CAR-Tregs from tonic signal-induced dysfunction

Abstract: The use of chimeric antigen receptor (CAR)-engineered regulatory T cells (Tregs) has emerged as a promising strategy to promote immune tolerance. However, in conventional T cells (Tconvs), CAR expression is often associated with tonic signaling, which can induce CAR-T cell dysfunction. The extent and effects of CAR tonic signaling vary greatly according to the expression intensity and intrinsic properties of the CAR. Here, we show that the 4-1BB CSD-associated tonic signal yields a more dramatic effect in CAR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 74 publications
2
44
2
Order By: Relevance
“…Studies in the delivery of chimeric antigen receptor (CAR) T cells in cancer (71, 72) and CAR Tregs in inflammatory models (73) have clearly shown that therapeutic success is reliant on dampening of memory acquisition and hindering the development of cellular exhaustion. CAR Tregs, while proposed for treatment of autoimmunity, likewise require methodological fine-tuning for prevention of exhaustion and loss of lineage stability (74). Future studies should investigate whether the incorporation of IL-2 + IGF1 or IL-7 + IGF1 into CAR Treg or Tconv expansion protocols, respectively, prevents exhaustion to allow for longer duration of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the delivery of chimeric antigen receptor (CAR) T cells in cancer (71, 72) and CAR Tregs in inflammatory models (73) have clearly shown that therapeutic success is reliant on dampening of memory acquisition and hindering the development of cellular exhaustion. CAR Tregs, while proposed for treatment of autoimmunity, likewise require methodological fine-tuning for prevention of exhaustion and loss of lineage stability (74). Future studies should investigate whether the incorporation of IL-2 + IGF1 or IL-7 + IGF1 into CAR Treg or Tconv expansion protocols, respectively, prevents exhaustion to allow for longer duration of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…4-1BB-containing CARs are more resistant to T-cell exhaustion [48]. Function is improved by exposure to mTOR inhibitors and vitamin C [45].…”
Section: -1bbmentioning
confidence: 99%
“…Furthermore, Lamarthee et al showed 4-1BB CAR Tregs exhibit decreased lineage stability and reduced in vivo suppressive capacities. Yet, transient exposure to mTOR inhibitors and vitamin C improves 4-1BB CAR Treg in vivo function [ 45 ]. In a separate study, Shrestha et al showed CAR Tregs generated with the 4-1BB domain are able to prevent GvHD in murine model [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dawson et al generated 10 CARs with different co‐receptor signaling domains and observed that CAR encoding CD28 were markedly superior to all other CARs in a murine model of CAR Treg therapy 35 . Interestingly, the 4‐1BB signaling domain was shown to be associated with tonic signaling in CAR Tregs which led to a decreased lineage stability and reduced in vivo suppressive capacities compared with CD28 CAR‐Tregs 36 . Transient ex vivo mitigation of 4‐1BB tonic signaling through mTOR inhibition significantly improved CAR‐Treg stability and function.…”
Section: Car Tregs Stability and Functionmentioning
confidence: 99%
“…35 Interestingly, the 4-1BB signaling domain was shown to be associated with tonic signaling in CAR Tregs which led to a decreased lineage stability and reduced in vivo suppressive capacities compared with CD28 CAR-Tregs. 36 Transient ex vivo mitigation of 4-1BB tonic signaling through mTOR inhibition significantly improved CAR-Treg stability and function. Because CAR Tregs stability and function depends on many parameters such as the characteristics of the cell donor, the source of Tregs, the isolation strategy and/or the CAR structure, each different CAR-Treg product can have a different stability and function.…”
Section: Car Tregs Stability and Functionmentioning
confidence: 99%